Pembuatan Biobriket dari Limbah Kayu UMKM Sebagai Energi Alternatif Rumah Tangga di Desa Bancer - As siddiqi, M. Jaza; Syafitri, Allichia Errika; Kurniawan, Sandhy; Farahdiansari, Ardana Putri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2025)
Teak wood is one of the main commodities in various regions of Indonesia. Many areas cultivate this wood due to the high demand, especially in the furniture industry. Teak wood is favored because it has high aesthetic and economic value. In Bancer Village, there are more than 10 furniture MSMEs, which can produce a total of 70 sacks of sawdust waste daily. The local community has not yet fully realized the potential of this sawdust waste. This community service aims to utilize sawdust waste into bio-briquettes, as an alternative fuel that can improve the local economy. Bio-briquettes are renewable, environmentally friendly alternative fuels. The implementation is carried out through several stages, including surveys, observations, bio-briquette making practices, and product evaluation. Surveys are conducted to determine the potential and needs of SMEs in Bancer Village. Observations are made to study the furniture production process and sawdust waste management. The making of bio-briquettes begins with burning sawdust into charcoal, mixing it with starch as a binder, molding the mixture, and drying it. The results of the community service show that the produced bio-briquettes have the potential as an environmentally friendly and economical alternative fuel. Socialization and training on bio-briquette making to SME owners and the Youth Organization of Bancer Village showed high enthusiasm.